Periodontal approach to improve Aesthetics : A Case Report - Vellayappan, Radha (Journal of Medical Biomedical and Applied Sciences, 2017)
A variety of factors including teeth form/position and gingival tissue levels may influence the overall smile aesthetics [1, 2]. In the last decade a great interest was focused on plastic periodontal surgery as a reliable tool to enhance esthetics